NETBEANS JAVA-BASED SCHOLARSHIP ADMISSION DECISION SUPPORT SYSTEM ON SMK INSAN TEKNOKRAT BEKASI - Fitriani, Ida; Pramarta, Pandu; Sutrisno, Danang (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This research aims to develop a Java NetBeans-based decision support system (SPK) for scholarship acceptance at Bekasi Insan Teknokrat Vocational School (Jaya Cimuning). This system uses the Simple Additive Weighting (SAW) method in the decision-making process to assess the eligibility of scholarship recipients based on certain criteria. The SAW method is integrated in the NetBeans Java development environment, and the results are evaluated for speed, accuracy, and user satisfaction level. This research resulted in a system that was successfully implemented, achieving an accuracy rate of 90% in assessing the eligibility of scholarship recipients. User evaluation shows a satisfaction rate of 85%, indicating a good user interface and ease of use of the system. This system makes a positive contribution to efficiency and transparency in the scholarship acceptance process at Bekasi Insan Teknocrat Vocational School. The research conclusion shows that this decision support system can be an effective tool in supporting the scholarship acceptance process. Development recommendations include improvements to the user interface, adding additional features, and further integration with the school's administrative systems. The results of this research provide a basis for further development in the field of decision support systems and their application in educational contexts.